2007
DOI: 10.1590/s0006-87052007000100019
|View full text |Cite
|
Sign up to set email alerts
|

Efeito de períodos de semeadura e das condições de armazenamento sobre a qualidade de grãos de feijão para o cozimento

Abstract: Appropriate preservation can maintain grain characteristics of recent harvested grains for larger period, assuring commercial value of the stored product. The objective of this study was to evaluate the effect of sowing periods on cooking quality of common bean grains of the TPS Nobre cultivar when stored under different temperatures, moisture content and storage times. A completely randomized design was applied, with three replications. The treatments were combinations of e three sowing periods, three storage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
0
15

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 11 publications
1
3
0
15
Order By: Relevance
“…Na semeadura realizada em 21/ 11/2003, foi observado maior porcentagem de grãos duros (10,22%), devido a menor disponibilidade hídrica verificada no sub-período floração-enchimento dos grãos. RIBEIRO et al (2007) também constataram maior porcentagem de grãos hardshell quando a semeadura da cultivar "TPS Nobre" foi realizada tardiamente na época de safra no Estado do Rio Grande do Sul.…”
Section: Resultsunclassified
See 2 more Smart Citations
“…Na semeadura realizada em 21/ 11/2003, foi observado maior porcentagem de grãos duros (10,22%), devido a menor disponibilidade hídrica verificada no sub-período floração-enchimento dos grãos. RIBEIRO et al (2007) também constataram maior porcentagem de grãos hardshell quando a semeadura da cultivar "TPS Nobre" foi realizada tardiamente na época de safra no Estado do Rio Grande do Sul.…”
Section: Resultsunclassified
“…Assim, a capacidade de hidratação dos grãos diminuiu progressivamente, pois, durante a estocagem, ocorreu a deterioração gradativa da qualidade dos grãos para o cozimento, caracterizada pelo aumento no grau de dureza dos grãos (BURR et al, 1968;ROZO et al, 1990;SARTORI, 1996). Entretanto, para a cultivar "TPS Nobre", quando armazenada por seis meses em câmara fria com 80% de umidade relativa do ar e com temperatura de 0,5 o C, não houve alteração na porcentagem de absorção de água, o que é desejável pelo fato de não provocar alteração na integridade do tegumento dos grãos (RIBEIRO et al, 2007).…”
Section: Resultsunclassified
See 1 more Smart Citation
“…Various authors have reported the existence of the genotype and environment interaction for this characteristic, with differences being observed in behavior of lines and cultivars in different locations, crop years and planting times (Carbonell et al, 2003;Ribeiro et al, 2007;Rodrigues et al, 2004;2005b). Bordin et al (2010) Therefore, the aim of this study was to assess the effect of different periods of the growing season on the technological quality of common bean grains.…”
Section: Introductionmentioning
confidence: 99%
“…O feijão é um produto que perde rapidamente o valor comercial após a colheita, principalmente pela redução da capacidade de reidratação, do aumento do tempo necessário de cozimento e do escurecimento do tegumento (RIBEIRO et al, 2007). Por este motivo, é necessário o desenvolvimento de cultivares com qualidades tecnológicas superiores, com menor tempo de cocção.…”
Section: Introductionunclassified